2017
DOI: 10.3390/ijms18010106
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Usefulness of Serum Total Bile Acid Concentrations in the Early Phase of Acute Pancreatitis of Varied Etiologies

Abstract: The most common causes of acute pancreatitis (AP) are biliary tract diseases with cholestasis and alcohol consumption. In 10%–15% of patients, etiology determination is difficult. Identification of the etiology allows for the implementation of adequate treatment. The aim of this study was to assess the utility of the serum concentrations of total bile acids (TBA) to diagnose AP etiology in the early phase of the disease. We included 66 patients with AP, admitted within the first 24 h from the onset of symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
0
16
2
Order By: Relevance
“… 4 – 6 Recent studies have demonstrated that serum total bile acid, serum neutrophil gelatinase-associated lipocalin and serum soluble Fms-like tyrosine kinase 1 might play a role in prediction of severity of AP. 7 9 …”
Section: Introductionmentioning
confidence: 99%
“… 4 – 6 Recent studies have demonstrated that serum total bile acid, serum neutrophil gelatinase-associated lipocalin and serum soluble Fms-like tyrosine kinase 1 might play a role in prediction of severity of AP. 7 9 …”
Section: Introductionmentioning
confidence: 99%
“…The cut-off values of 4.7 mol/L, with a diagnostic accuracy of 85%. However, circulating TBA had nothing to do with the severity of AP [15].…”
Section: Discussionmentioning
confidence: 96%
“…Dysregulation of BAs transport and impaired BAs receptor signalling may contribute to the pathogenesis of some metabolic diseases such as non-alcoholic fatty liver disease, obesity, type 2 diabetes, and atherosclerosis [14]. The circulating TBA levels are maintained within a certain range under physiological conditions, generally 2-10 μmol/L [15], but in some states of diseases, the levels of circulating TBA will exceed the threshold. An increase in circulating TBA is predominately detected in several hepatobiliary diseases.…”
mentioning
confidence: 99%
“…Acute pancreatitis (AP) caused approximately 275,000 hospitalizations in 2009 (more than a 2-fold increase since 1982), and it is the single most frequent gastrointestinal cause of hospital admissions in the United States (Peery et al 2012). The reason for this is its diverse aetiology and the unpredictable course of the disease (Maleszka et al 2017). The aetiology, pathogenesis, and progression of acute pancreatitis are the subjects of numerous experimental and clinical studies (Tomaszewska et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of AP, apart from alcohol abuse and cholelithiasis, may also include a vascular component responsible for pancreatic ischaemia (Tomaszewska et al 2000). However, the most frequent aetiology is cholelithiasis, which accounts for 30-60% of cases (Maleszka et al 2017).…”
Section: Introductionmentioning
confidence: 99%